Prediction of Financial Distress in Manufacturing Companies: Evidence from Indonesia - Iskandar Bukhori; Rita Kusumawati; Meilani Meilani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to examine the effect of liquidity ratios, activity ratios, leverage ratios, and sales growth as predictors of financial distress before the bankruptcy stage.Design/Methodology/Approach: The samples of this study included manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2019. The samples were selected using the purposive sampling method, and 334 sample companies were obtained. Then, the data analysis employed logistic regression.Research findings: The results revealed that all financial ratios investigated in this study significantly affected financial distress. In addition, while the liquidity ratio, activity ratio, and sales growth had a significant negative effect, the leverage ratio had a significant positive impact on financial distress.Practical and Theoretical contribution/Originality: Currently, most research on bankruptcy has concentrated on bankrupt companies, which are the final phase of the financial distress stage. Meanwhile, the current study attempts to address the gap by researching financial distress prediction before the bankruptcy stage.Practitioner/Policy implications: The results of this study are expected to help stakeholders to take corrective action early to prevent financial distress to the bankruptcy stage.Research limitation: The study only used a negative profit period of two years, at the stage of severe liquidity, and utilized four years of data in one industry sector.